2007
DOI: 10.1103/physreva.75.033619
|View full text |Cite
|
Sign up to set email alerts
|

Radiation of linear waves in the stationary flow of a Bose-Einstein condensate past an obstacle

Abstract: Using stationary solutions of the linearized two-dimensional Gross-Pitaevskii equation, we describe the "ship wave" pattern occurring in the supersonic flow of a Bose-Einstein condensate past an obstacle. It is shown that these "ship waves" are generated outside the Mach cone. The developed analytical theory is confirmed by numerical simulations of the flow past body problem in the frame of the full non-stationary Gross-Pitaevskii equation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
62
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 14 publications
11
62
1
6
Order By: Relevance
“…An analytic discussion of their shape is discussed in detail in [41]; their one-dimensional restriction was first mentioned in [40]. In the next section we shall present analytical formulas for an approximated theory where the single particle region of the Bogoliubov dispersion is modeled with the parabolic dispersion of single-particle excitations.…”
Section: Superfluidity Vs Bogoliubov-cerenkov Wakementioning
confidence: 99%
“…An analytic discussion of their shape is discussed in detail in [41]; their one-dimensional restriction was first mentioned in [40]. In the next section we shall present analytical formulas for an approximated theory where the single particle region of the Bogoliubov dispersion is modeled with the parabolic dispersion of single-particle excitations.…”
Section: Superfluidity Vs Bogoliubov-cerenkov Wakementioning
confidence: 99%
“…It means that similar computation methods [18,19] can be used in the case of Bose-Einstein condensate. In [16] such a theory was developed and shape of waves crests was obtained. It was shown that this theory agrees very well with numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the elementary characteristics of these structures were derived from the dispersion law (1). In the paper [16] it was noticed that these waves have a physical origin analogous to Kelvin's ship waves [17] generated by a ship moving in a still water. It means that similar computation methods [18,19] can be used in the case of Bose-Einstein condensate.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the critical velocity at which superfluid behavior breaks down is about V c ∼ = 0.35c s , where c s denotes the sound velocity in a uniform condensate far enough from the obstacle. For the flow velocity above the sound velocity, V > c s , a new channel of dissipation opens-Cherenkov radiation of Bogoliubov waves whose interference results in formation of a specific "ship wave" pattern located, due to the properties of the Bogoliubov dispersion relation, outside the Mach cone [6][7][8][9]. Emission of vortices dominates in the interval of velocities c s < V < 1.43c s where vortices form so-called "vortex streets" located inside the Mach cone.…”
mentioning
confidence: 99%